Cloning and Functional Characterization of a Pericarp Abundant Expression Promoter (AhGLP17-1P) From Peanut (Arachis hypogaea L.) - Sharif, Yasir; Chen, Hua; Deng, Ye; Ali, Niaz; Khan, Shahid Ali; Zhang, Chong; Xie, Wenping; Chen, Kun; Cai, Tiecheng; Yang, Qiang; Zhuang, Yuhui; Raza, Ali; et al. (Frontiers in Genetics, 2022)
Peanut (Arachis hypogaea L.) is an important oil and food legume crop grown in tropical and subtropical areas of the world. As a geocarpic crop, it is affected by many soil-borne diseases and pathogens. The pericarp, an inedible part of the seed, acts as the first layer of defense against biotic and abiotic stresses. Pericarp promoters could drive the defense-related genes specific expression in pericarp for the defense application. Here, we identified a pericarp-abundant promoter (AhGLP17-1P) through microarray and transcriptome analysis. Besides the core promoter elements, several other important cis-elements were identified using online promoter analysis tools. Semiquantitative and qRT-PCR analyses validated that the AhGLP17-1 gene was specifically expressed only in the pericarp, and no expression was detected in leaves, stem, roots, flower, gynophore, testa, and embryo in peanut. Transgenic Arabidopsis plants showed strong GUS expression in siliques, while GUS staining was almost absent in remaining tissues, including roots, seedlings, leaf, stem, flowers, cotyledons, embryo, and seed coat confirmed its peanut expressions. Quantitative expression of the GUS gene also supported the GUS staining results. The results strongly suggest that this promoter can drive foreign genes' expression in a pericarp-abundant manner. This is the first study on the functional characterization of the pericarp-abundant promoters in peanut. The results could provide practical significance to improve the resistance of peanut, and other crops for seed protection uses.